ANALISIS POTENSI BPRS TERHADAP PENINGKATAN OMSET USAHA MENENGAH KECIL DAN MIKRO (UMKM) DI KABUPATEN BIREUEN Studi Kasus : PT. BPRS Rahmania Dana Sejahtera - Junardi, Junardi; Azhari, Azhari (IndOmera, 2020)
This study aims to determine how much influence the Third Party Fund, Asset To Micro, Small and Medium Enterprises (UMKM) through UMKM financing in Bireuen Regency by taking PT. BPRS Rahmania Dana Sejahtera as a case study. This type of research uses quantitative approach, namely research based on numbers and statistical analysis. This type of quantitative research is included in descriptive research. Data used in this research is secondary data, by collecting annual published financial reports of PT. BPRS Rahmania Dana Sejahtera from 2010 to 2019 per quarter, which is time series data. Data then classified based on existing criteria determined. These data are obtained from the official website of Otoritas Jasa Keuangan www.ojk.go.id. Because the object of research observation is the amount of turnover UMKM, then the population in this study were PT. BPRS Rahmania Dana Sejahtera’s customers which already uses financing services from 2010 to 2019. And due to data limitations, then all population data is sampled. The analysis technique used is path analysis method. The results of this study is total third party fund influence positive and significant on financing of UMKM amounted to 46,46%. There is a positive and significant influence between assets to UMKM financing amounted 51,27%. There is a positive and significant influence between third party fund and assets to UMKM financing amounted 97,7%. Then there is a positive and significant influence between UMKM financing on UMKM turnover amounted 98%. And there is a positive and significant influence of third party fund to assets amounted 94%